Architectural design criteria for multi-storey housing buildings - Kuan, Y.; Yahaya, A. (Open House International Association, 2016)
Architecture influences people and the environment from the past, present and the future. Nevertheless architecture and design quality is viewed as subjective, and benchmarks to achieve consensus are necessary for design or evaluation of buildings. This paper establishes architectural design criteria for design quality of multi-storey housing buildings. A set of the criteria was established with literature review, an operational definition and survey on qualified persons or architects in the professional practice of architecture. The literature reviews identified seven concepts for architecture and design quality, and the operational definition translated this architectural design quality to measurable and observable cases and variables. The survey collected these variable data from a purposive sample of 95 respondents, and these data were examined by statistical analysis. The results of the descriptive statistics, inferential t-tests (p ≤ 0.05) and positive hypothesis testing verified that respondents in general agreed to these seven design concepts as architectural design criteria for design quality. These results established the first ever set of seven architectural design criteria which were ranked in descending order of significance as function, socio-culture, site context, cost, aesthetic of art, sustainability, and Feng Shui. These architectural design criteria can be applied to the design or evaluation of multi-storey housing buildings for the good of people and the environment.